Inclusion of Cohabitation Law in Article 412 of Law Number 1 of 2023 in the Perspective of Applicable Norms in Indonesia - Refangga, Galih Setyo; Sujiantoro, Sujiantoro (PT FORMOSA CENDEKIA GLOBAL, 2024)
This endeavor will also facilitate the restoration of relationships, particularly those between adult men and women living together within the sanctity of marriage, governed by Article 412. The objective of this research is to examine the legal implications arising from Criminal Code Article 412. The study shows that using Article 412 of the Criminal Code might clash with religious, moral, and legal rules. It may also clash with Law Number 1 of 2023, which says that national law and regional rules may have different interpretations of legal rules. This recognition of coexisting legal systems within the community creates numerous legal ambiguities that may pose challenges for society.